2005
DOI: 10.1186/1471-2105-6-267
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clustered microRNAs using an ab initio prediction method

Abstract: BackgroundMicroRNAs (miRNAs) are endogenous 21 to 23-nucleotide RNA molecules that regulate protein-coding gene expression in plants and animals via the RNA interference pathway. Hundreds of them have been identified in the last five years and very recent works indicate that their total number is still larger. Therefore miRNAs gene discovery remains an important aspect of understanding this new and still widely unknown regulation mechanism. Bioinformatics approaches have proved to be very useful toward this go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(91 citation statements)
references
References 32 publications
1
89
0
1
Order By: Relevance
“…Berezikov et al (2005) showed that miR-451 (which they had designated ''Cand919'') was not expressed in mouse ES cells but was expressed in adult mouse brain and also in increasing amounts through embryonic stages (8.5 dpc < 12.5 dpc < 16.5 dpc). miR-451 has also been described by others (Altuvia et al 2005;Sewer et al 2005), but never in the context of human blood cells. We find that there is considerable heterogeneity of the 39-end of miR-451 with many miR-451 molecules being longer than most miRNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Berezikov et al (2005) showed that miR-451 (which they had designated ''Cand919'') was not expressed in mouse ES cells but was expressed in adult mouse brain and also in increasing amounts through embryonic stages (8.5 dpc < 12.5 dpc < 16.5 dpc). miR-451 has also been described by others (Altuvia et al 2005;Sewer et al 2005), but never in the context of human blood cells. We find that there is considerable heterogeneity of the 39-end of miR-451 with many miR-451 molecules being longer than most miRNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test this, the 19 pre-miRNA sequences were analyzed using miR-abela, a program optimized to predict human pre-miRNAs (Sewer et al 2005). The program predicted that 17 of the pre-miRNA structures were human pre-miRNA-like (Supplemental Figs.…”
Section: Identification Of Mirnas In D Discoideummentioning
confidence: 99%
“…To identify pre-miRNA structures, sequences from 200 nt upstream of to 200 nt downstream from a mapped location were extracted and analyzed using MiRfold (Billoud et al 2005;Boccara et al 2007) with standard settings (default temperature 22°C, the growth temperature for D. discoideum). Pre-miRNA structures identified by MiRfold with a penalty <5 and a DG-value per nt <À0.4 kcal/mol were considered as premiRNA candidates and were subsequently reanalyzed with miR-abela (Sewer et al 2005) (http://www.mirz.unibas.ch/cgi/pred_miRNA_ genes.cgi). Further analyses are described in Results.…”
Section: Mirna Analysismentioning
confidence: 99%
“…Xie et al (2005) reported a target-sequence-driven approach in which hairpin structures are considered to be miRNA candidates if they have conserved motifs that are reverse-complements of sequence segments overrepresented in conserved 39-UTRs. Methods that do not rely on sequence conservation have been reported (Sewer et al 2005;Xue et al 2005;Yousef et al 2006) in which detailed structural and nucleotide sequence features such as nucleotide frequency, length of predicted stem, and size of symmetric bulges are used as the features of machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%